2012
DOI: 10.1109/tii.2012.2205699
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Incremental Modeling Based on Least Squares and Fuzzy $K$-NN for Monitoring Tool Wear in Turning Processes

Abstract: Abstract-There is now an emerging need for an efficient modeling strategy to develop a new generation of monitoring systems. One method of approaching the modeling of complex processes is to obtain a global model. It should be able to capture the basic or general behavior of the system, by means of a linear or quadratic regression, and then superimpose a local model on it that can capture the localized nonlinearities of the system. In this paper, a novel method based on a hybrid incremental modeling approach i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Hybrid Incremental Modeling (HIM) aims to provide an approximation of the behavior of a locally nonlinear system [16]. To that end, the strategy uses a global model that captures the basic or general behavior of the system and then superimposes a local model on it that captures the local behavior.…”
Section: Hybrid Incremental Modelingmentioning
confidence: 99%
“…Hybrid Incremental Modeling (HIM) aims to provide an approximation of the behavior of a locally nonlinear system [16]. To that end, the strategy uses a global model that captures the basic or general behavior of the system and then superimposes a local model on it that captures the local behavior.…”
Section: Hybrid Incremental Modelingmentioning
confidence: 99%
“…All these three forces contain the information of tool wear while their sensitivities to the tool wear condition are different when applied in different methods. In [11], the thrust cutting force is found to be most sensitive when applying the singularity analysis, while Penedo et al [33] chose the twisting force Fz to monitor the tool wear by a hybrid incremental model, and in [32], all the forces in three directions were applied. In this work, since the cutting force fluctuates a lot in cutting the Inconel 718 material, its amplitude would not be applied.…”
Section: Tool Wear Process In Machiningmentioning
confidence: 99%
“…Up to date, monitoring systems of industrial processes have demonstrated the importance and economic benefits of the application of network-based solutions and Artificial Intelligence techniques [1][2][3]. Monitoring of infrastructures is essential to build the next generation of predictive models.…”
Section: Introductionmentioning
confidence: 99%